A Platform Studies Approach to the Role of Technology in the ICTD Ecosystem: The SMS in m4d Interventions. (30th August 2016) - Loudon, Melissa
Abstract : We have good evidence – not least from widespread adoption – that mobile communications can improve the lives of the poor. Building on this success, interventions using mobile technology to tackle development problems have become common in ICT4D. The short message service (SMS), which works on even basic phones, is a popular platform for mobiles for development (m4d) apps and services. This paper documents the historical origins and technical characteristics of SMS as a platform for m4d interventions, demonstrating how inherent technological rigidities in the platform combine with creative adaptation, appropriation and re-use to produce a particular set of affordances and constraints. I argue that optimism about the potential for new technologies to contribute to development should be tempered by awareness that the developing world is seldom the intended audience of technology development. Approaches from the social construction of technology – infrastructure studies and platform studies – contribute to a holistic and historicized understanding of the role of technology in the information and communication technology ecosystem.